2022
DOI: 10.1002/adfm.202210328
|View full text |Cite
|
Sign up to set email alerts
|

Lattice and Surface Engineering of Ruthenium Nanostructures for Enhanced Hydrogen Oxidation Catalysis

Abstract: Ru has recently been considered as a promising alternative of Pt toward hydrogen oxidation reaction (HOR) due to its lower price and similar hydrogen binding energy (HBE) in comparison to Pt. Nevertheless, the catalytic performance of Ru toward HOR is far from the satisfaction of practical application. Herein, it is demonstrated that the modification of Ru multi‐layered nanosheet (MLNS) with Ni can significantly promote the HOR performance. In particular, the HOR performance is strongly related to the Ni locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…The formation of MoNi 4 nanosheet arrays coated on the surface of MoO 2 cuboid arrays improves the surface oxophilicity that can promote water adsorption and activation, boosting the higher nonacidic hydrogen kinetics. [ 43‐46 ] This was further evidenced by the XPS signal peaks of O 1s (Figure 2f), in which the peaks at 531.3, 533, and 530.1 eV are deconvoluted to adsorbed H 2 O, adsorbed OH (OH ads ), and M—O, respectively. [ 22 ] When compared with MoO 2 /MoNi 4 cuboid nanosheet arrays (Figure S10d), hierarchical MoO 2 /MoNi 4 @Ru/ RuO 2 heterogeneous nanosheet arrays possessed a greater amount of M—O bond, suggesting its enhanced adsorption of H 2 O and OH ads that improves the electrolysis of water.…”
Section: Resultsmentioning
confidence: 93%
“…The formation of MoNi 4 nanosheet arrays coated on the surface of MoO 2 cuboid arrays improves the surface oxophilicity that can promote water adsorption and activation, boosting the higher nonacidic hydrogen kinetics. [ 43‐46 ] This was further evidenced by the XPS signal peaks of O 1s (Figure 2f), in which the peaks at 531.3, 533, and 530.1 eV are deconvoluted to adsorbed H 2 O, adsorbed OH (OH ads ), and M—O, respectively. [ 22 ] When compared with MoO 2 /MoNi 4 cuboid nanosheet arrays (Figure S10d), hierarchical MoO 2 /MoNi 4 @Ru/ RuO 2 heterogeneous nanosheet arrays possessed a greater amount of M—O bond, suggesting its enhanced adsorption of H 2 O and OH ads that improves the electrolysis of water.…”
Section: Resultsmentioning
confidence: 93%
“…Hydrogen is a high energy density carrier that can effectively alleviate human dependence on fossil energy and facilitate the realization of carbon neutrality. In recent years, electrocatalytic hydrogen evolution reaction (HER) has been a promising high-purity hydrogen production technology, attracting a large number of researchers’ research interest. , Until now, the platinum-based electrocatalysts show high activity for electrocatalytic HER, while their widespread use has been severely hampered by the scarcity of resources and high prices , Thus, it is essential to synthesize Pt-free HER catalysts with excellent HER performance in alkaline solutions. , …”
Section: Introductionmentioning
confidence: 99%
“…5,6 Until now, the platinum-based electrocatalysts show high activity for electrocatalytic HER, while their widespread use has been severely hampered by the scarcity of resources and high prices 7,8 Thus, it is essential to synthesize Pt-free HER catalysts with excellent HER performance in alkaline solutions. 9,10 The optimized d-band electronic structure makes Ru has a hydrogen binding capacity similar to Pt (∼65 kcal mol −1 ), but its price is far lower than Pt, 11,12 and it is chemically inert to aggressive electrolytes, making it a promising alternative to Pt. 13 In particular, the modulation of metal Ru by nonmetallic anions can promote the desorption of H to a certain extent.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[26] On this basis, enhancing the OHBE of catalysts though introducing oxyphilic sites has been considered as an efficient approach to promote their catalytic activities toward alkaline HOR. [27][28][29][30] Unfortunately, the exact role of OHBE for alkaline HOR is still elusive. Moreover, regulating the RDS of alkaline HOR through enhancing the OHBE of electrocatalysts to accelerate the reaction kinetics, has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that the moderately enhanced OHBE can lower the energy barrier of the water dissociation step, which has been often considered as the rate‐determining step (RDS), and thereby accelerate the alkaline HER kinetics, through changing the RDS of alkaline HER from water dissociation step to OH ad desorption step [26] . On this basis, enhancing the OHBE of catalysts though introducing oxyphilic sites has been considered as an efficient approach to promote their catalytic activities toward alkaline HOR [27–30] . Unfortunately, the exact role of OHBE for alkaline HOR is still elusive.…”
Section: Introductionmentioning
confidence: 99%